Ecological impacts of biological invasions on native birds in Africa - Gichohi, Nathan W (Percy FitzPatrick Institute of African Ornithology, 2014)
The impacts of biological invasions on native avian diversity have been the subject of many studies in Africa. However, a holistic synthesis of available information from different taxa and their impacts on native birds is lacking. From published information, I analysed the negative and positive effects of biological invaders on native African birds from five taxa: plants, invertebrates, fish, mammals and birds. In order to assess functional gains and losses, native birds were categorized into their functional guilds defined by their primary diet. I limited my scope to mainland Africa at the biome level. ArcView GIS 3.3 software was used to map locational data of impacts within the major biomes. The results indicate that a minimum of 572 native birds are negatively impacted by invasive species from the five taxa. This represents ca 29% of all the bird species in Africa. In contrast, only 191 species of native birds benefited from such invasions. Birds whose diet was primarily insects were disproportionally impacted. The majority of the impacts were caused by invasive plants. At the biome level, the greatest numbers of native birds impacted were in the Montane grassland and shrubland biome. It is predicted that native birds will continue to lose more than they gain from biological invasions in the continent.